Acronym-Based Communication in Cross-Cultural Meetings: A Narrative Study of Human Resources Professionals in Jakarta - Octa Pratama Putra; Abdul Qayoum Safi; Fadilah Fadilah (J-Lalite: Journal of English Studies, 2026)
This study explores the use of acronym-based communication strategies by HR (Human Resources) professionals during presentations to foreign clients. Delivering presentations in English within cross-cultural professional settings presents challenges for non-native speakers; including language proficiency, cultural nuances, and performance anxiety. Guided by Cross-Cultural Communication theory, this study examines how acronyms can bridge cultural gaps and enhance clarity. It also draws on the language and acronym theory, which views acronyms as cognitive-linguistic tools that aid in simplifying complex ideas, improving retention, and supporting fluent discourse. To investigate this phenomenon, a descriptive qualitative design was employed by using the narrative inquiry to explore the lived experience of an HR staff member at a multinational company in Jakarta. The participant shared reflective stories about preparing and delivering presentations using acronym-based methods. Findings reveal that acronyms help structure content, reduce stress, and engage international audiences more effectively. Furthermore, their use minimizes ambiguity and supports intercultural understanding. The study concludes that acronym-based strategies offer practical benefits for enhancing communication in global workplace settings; particularly for HR professionals who frequently engage in English-language and cross-cultural interactions.